2011
DOI: 10.3109/00498254.2010.545452
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and metabolism of BIBF 1120 after oral dosing to healthy male volunteers

Abstract: The pharmacokinetics and metabolism of BIBF 1120, an oral triple angiokinase inhibitor targeting vascular endothelial growth factor receptor (VEGFR), platelet-derived growth factor receptor (PDGFR), and fibroblast growth factor receptor (FGFR), were studied in healthy male volunteers (n = 8) who had received a single oral dose of 100 mg [(14)C]-radiolabelled BIBF 1120 administered as solution. BIBF 1120 was well-tolerated and rapidly absorbed; median time to reach maximum plasma concentrations was 1.3 h and gM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(116 citation statements)
references
References 18 publications
4
111
1
Order By: Relevance
“…BIBF 1202 ZW is subsequently glucuronidated by various uridine diphosphate glucuronosyltransferases (UGTs) in the intestine and by UGT1A1 in the liver to form BIBF 1202 glucuronide. Both nintedanib metabolites are excreted via the biliary system into the faeces [13]. This phase II study was conducted to determine the safety, tolerability and pharmacokinetics of nintedanib and its metabolites, alone and when added to ongoing pirfenidone therapy, in Japanese patients with IPF.…”
Section: Introductionmentioning
confidence: 99%
“…BIBF 1202 ZW is subsequently glucuronidated by various uridine diphosphate glucuronosyltransferases (UGTs) in the intestine and by UGT1A1 in the liver to form BIBF 1202 glucuronide. Both nintedanib metabolites are excreted via the biliary system into the faeces [13]. This phase II study was conducted to determine the safety, tolerability and pharmacokinetics of nintedanib and its metabolites, alone and when added to ongoing pirfenidone therapy, in Japanese patients with IPF.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraging PFS data in OC have been reported (Table 2), and OS data for this indication are awaited [92]. Nintedanib is an orally available angiokinase inhibitor of VEGFR-1 to -3, PDGFR-a and -b, and FGFR-1 to -3, in addition to FLT-3 and Src [82,114,138]. Human tumor model studies show that nintedanib can reduce vessel density, vessel integrity, and tumor growth via effects on endothelial and smooth muscle cells, pericytes, and tumor cells [82].…”
Section: Current and Emerging Multitargeting Antiangiogenic Agentsmentioning
confidence: 99%
“…The renal excretion plays a negligible role in Nintedanib elimination, as preclinical data showed that the major route of elimination of [C 14 ] Nintedanib is via fecal and biliar excretion, amounting to 93.4% of dose [31].…”
Section: Pharmacokineticsmentioning
confidence: 99%